A customs union with multinational firms: the automobile market in Argentina and Brazil - Brambilla, Irene (2005)
This paper looks empirically into the behavior of multinational firms in international oligopolistic markets with trade balance constraints. I show how a particular form of non-tari barrier applied at the firm level can lead to an increase in trade flows in the presence of intra-firm strategic trade. In my application, I estimate a model of demand, supply and trade policy in the automobile sector in Argentina and Brazil during 1996-1999. I measure the economic impact of a trade balance constraint that was in eect during that period and I compute predicted economic outcomes for the full adoption of a customs union, as has been agreed as part of the Mercosur negotiations, separating the sometimes opposing impacts of the removal of non-tari